Particle size dependence on the structural, transport and optical properties of charge-ordered Pr0.6Ca0.4MnO3 - Kumar S.; Dwivedi G.D.; Lourembam J.; Kumar S.; Saxena U.; Ghosh A.K.; Chou H.; Chatterjee S. (My University, 2025)
Abstract Structural, transport and optical properties of nano-crystalline Pr0.6Ca0.4MnO3 have been investigated to emphasize on the semiconducting properties of charge-ordered manganite. Rietveld refinement of X-ray diffraction pattern of Pr0.6Ca0.4MnO3 nanoparticles show that due to increase in sintering temperature, MnO6 octahedra elongated along z-direction and compressed in x-y plane. Both Mn-O-Mn angles are found to decrease with increasing sintering temperature. Fourier transform infrared (FTIR) spectroscopy measurements reveal that the stretching and bending vibration of Mn-O-Mn is responsible for the change in Mn-O-Mn bond length and bond angle respectively. With increasing sintering temperature, these vibrations tend to increase, which resulted in the further distortion of MnO6 octahedra. Magnetic measurements suggest that charge ordering is established and system becomes antiferromagnetic with increasing particle size. Resistivity behavior of Pr0.6Ca0.4MnO3 nanoparticles clearly exhibit semiconducting nature of these systems, which is due to the formation of charge-ordered state of Mn3+ and Mn4+. Estimated optical band-gap of ∼3.7 eV for Pr0.6Ca0.4MnO3 nanocrystals, makes it a potential candidate for wide band-gap magnetic semiconductors. © 2015 Published by Elsevier B.V.